A Tale of Three Lives: The seductions of a Research Fellow, a Pallid Harrier and a Collared Dove - Rautio, Pauliina (Reconceptualizing Educational Research Methodology, 2022)
The objective of this paper is to bring into the open some of the often implicit and/or improper forces of various kinds of seductions in doing (post)qualitative inquiry. To ask how we view and understand ourselves as professionals and animals with a desire to breed. Whether we are seduced by our own reflections or by the phenomena calling to be transformed – or always both.